2015
DOI: 10.1007/s00253-015-7009-z
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting microbial community composition and function perspective in sections of a full-scale coking wastewater treatment system

Abstract: To characterize the microbial community of the coking wastewater (CWW) treatment system and to study the effects of CWW characteristics and operational parameters on microbial communities, active sludge samples were collected from a full-scale CWW treatment plant using three-phase fluidized bed biological reactors. High-throughput MiSeq sequencing was used to examine the 16S rRNA genes of microbiology, revealing a distinct microbial composition among the active sludge samples of three sequential bioreactors. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 54 publications
5
15
1
Order By: Relevance
“…2 and Table 1, anaerobic treatment removed over one third of COD and TOC, and more than half of phenolic derivatives and NHCs, showing that the anaerobic processes could play an important role in the treatment of CWW. The results of this study are consistent with those of Wang et al (2011) and Zhu et al (2016) who showed 20-30 % COD removal by mesophilic anaerobic treatment. The removal of total phenols (54.0 %) and phenolic derivatives (58.4 %) was achieved in the present study, and were considerably higher than that achieved in previous studies (Wang et al 2011, 20-30 %;Zhu et al 2016, 18.0 %), which might be partly due to the longer HRT (42 h) applied in this study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…2 and Table 1, anaerobic treatment removed over one third of COD and TOC, and more than half of phenolic derivatives and NHCs, showing that the anaerobic processes could play an important role in the treatment of CWW. The results of this study are consistent with those of Wang et al (2011) and Zhu et al (2016) who showed 20-30 % COD removal by mesophilic anaerobic treatment. The removal of total phenols (54.0 %) and phenolic derivatives (58.4 %) was achieved in the present study, and were considerably higher than that achieved in previous studies (Wang et al 2011, 20-30 %;Zhu et al 2016, 18.0 %), which might be partly due to the longer HRT (42 h) applied in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Table 1 and Table S1 reveal that the combined anaerobic-aerobic system removed almost all phenol derivatives and NHCs along with significant removal of COD (81.8 %), SCN − (98.2 %), and CN − (85.4 %). The overall removal efficiency achieved in this study is in agreement with that obtained in previous studies (Zhu et al 2016;Sharma and Philip 2015;Jin et al 2013;Lai et al 2008;Maranon et al 2008), showing COD, total phenol, and SCN − removals of 63.0-86.5 %, 98.0-100.0 %, and 90.0-98.0 %, respectively, in integrated anaerobic-anoxic-aerobic treatment systems with or without sludge recirculation. Thus, the combined process not only significantly saved aeration energy but ensured better system stability when encountering fluctuations in wastewater compositions and toxic load (Chakraborty and Veeramani 2002).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations